2022
DOI: 10.3390/ijerph19148699
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes and Cardiovascular Diseases Risk Assessment in Community Pharmacies: An Implementation Study

Abstract: The implementation of a new service is often challenging when translating research findings into routine clinical practices. This paper presents the results of the implementation study of a pilot project for a diabetes and cardiovascular diseases risk-assessment service in Belgian community pharmacies. To evaluate the implementation of the service, a mixed method was used that follows the RE-AIM framework. During the testing stage, 37 pharmacies participated, including five that dropped out due to a lack of ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…This research complements a first study in Belgium examining the feasibility of offering a risk-assessment service for diabetes and cardiovascular diseases in community pharmacies and the factors influencing its implementation. Descriptive details on the methodology of the risk assessment, results of the implementation study and its feasibility in practice were reported by Rondeaux et al [12]. Our present study aimed to develop materials to support pharmacists in their new role of providing a risk assessment service to their patients.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…This research complements a first study in Belgium examining the feasibility of offering a risk-assessment service for diabetes and cardiovascular diseases in community pharmacies and the factors influencing its implementation. Descriptive details on the methodology of the risk assessment, results of the implementation study and its feasibility in practice were reported by Rondeaux et al [12]. Our present study aimed to develop materials to support pharmacists in their new role of providing a risk assessment service to their patients.…”
Section: Discussionmentioning
confidence: 98%
“…The development procedure was inspired by the basic steps for developing health education tools using a user-centred approach [11,12]. The development of the materials involved a multistep process, including a need assessment phase involving a literature review and discussions with stakeholders, and a creative design phase followed by the evaluation of the materials created.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, there is a raising interest in involving community pharmacists in the prevention of skin cancer [ 45 47 ]. Belgium has a dense and accessible pharmacy network [ 48 – 50 ]. However, it is unclear which persons could be reached by Belgian community pharmacists for skin cancer awareness.…”
Section: Introductionmentioning
confidence: 99%